Coastal Tourism Development and Sustainability: A Global and Indonesian Perspective - Adnyawati, Ida Ayu Agung (Bali Tourism Board, 2025)
Coastal tourism represents one of the fastest-growing segments of the global tourism industry, offering significant economic benefits while simultaneously intensifying environmental and social pressures. This study synthesizes global and Indonesian perspectives on the dynamics of coastal tourism development and sustainability, emphasizing the interplay between climate change, governance, and local community engagement. Using a qualitative synthesis approach, the research integrates findings from peer-reviewed studies, policy reports, and empirical case analyses. Key analytical frameworks, including the SWOT Analysis, Coastal Hazard Wheel (CHW), and Coastal Vulnerability Index (CVI) are examined to assess both environmental hazards and socio-economic dimensions of tourism development. Findings highlight that coastal destinations worldwide face “triple pressures” from mass tourism, climate-induced hazards, and infrastructure overdevelopment. In Indonesia, sites such as Loang Baloq Beach in Lombok illustrate the dual potential of heritage-based and community-driven coastal tourism when aligned with sustainable management principles. The study also explores the emerging concept of blue tourism, which integrates marine conservation with sustainable economic use under the national Blue Economy agenda. This model promotes participatory governance, ecosystem restoration, and low-carbon operations as pathways toward regenerative tourism. It argues that sustainable coastal tourism requires a multidimensional approach that combines scientific assessment tools, local wisdom, and cross-sectoral policy coordination. Such an integrated framework ensures resilience, enhances community welfare, and contributes to achieving the Sustainable Development Goals (SDGs), particularly those related to climate action and ocean sustainability.